Role and Significance of Hematological parameters in Diabetes Mellitus - Farooqui, Rafae; Afsar, Nabila; Afroze, Idrees Akhtar (Annals of Pathology and Laboratory Medicine, 2019)
Background: Diabetes mellitus is a global metabolic disorder characterized by persistent hyperglycemia and increased risk of microvascular and macrovascular complications. Consistent elevation of HbA1c can be associated with functional and structural changes in hemoglobin molecule, cytoplasmic viscosity and osmotic disturbances within red cell. These changes may be reflected in the red cell analytical parameters. Methods: 120 subjects were studied. 41 were non diabetic healthy subjects (Group1). 79 were known diabetic patients, divided into two groups: HbA1c <7(39 subjects) Group 2 and HbA1c >7(40 subjects) Group 3. Sample for glucose estimation and CBC were collected in vacutainers containing sodium Fluoride and K 2EDTA respectively. Glucose, HbA1c and CBC estimation was carried out by auto analyzers. Result: Mean RBC count of diabetics with HbA1c<7 was less when compared to non-diabetic individuals. Significant decrease was noted in the mean RBC count, Hb, HCT and MCV of diabetics with HbA1c>7 when compared to non diabetic individuals. There was significant decrease in mean Hb, HCT, MCV, MCH of diabetics with HbA1c >7 when compared to diabetics with HbA1c <7. Conclusion: The findings in the present study suggest that diabetic patients with poor control are more prone to develop anemia. This indicates a need for routine CBP examination for early detection and management of anemia in diabetic patients at the primary care setting to reduce associated morbidity due to lowered immunity associated with anemia and complications such as diabetic ketoacidosis.